FINANCIAL LITERACY, OVERCONFIDENCE, DAN HERDING PADA KEPUTUSAN INVESTASI DI PASAR MODAL - Milati, Yuwinda Meysella; Zen, Faida (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.10.TAHUN.2022DO - 10.24843/EEB.2022.v11.i10.p10, 2022)
Investment can be interpreted as the allocation of some of the assets owned so as to generate profits in the future. There are various factors that can influence a person when making investment decisions. The purpose of this research is to identify several factors that influence an investor in making investment decisions. These factors are financial literacy, overconfidence, and herding. The object of this research is capital market investors who are actively transacting for more than one year with a total sample of 140 respondents taken by purposive sampling method with certain criteria. Data was collected using a questionnaire by utilizing the Google Forms platform which was distributed through WhatsApp groups. The analytical tool used is multiple linier regression. The findings of this research indicate that financial literacy and herding have a positive and significant effect, while overconfidence does not affect an investor in making investment decisions in the capital market.